(untitled) (Bangladesh Medical Journal, 2021)
The Wuhan City of China evidenced unknown aetiology pneumonia cases at the end of December 2019. On 7 January 2020, the causative agent was identified as a novel coronavirus (2019-nCoV), currently referred to as SARS-CoV-2, and coronavirus disease as COVID-19. Older adults and people of any age who have underlying medical conditions, such as hypertension and diabetes, have shown worse prognosis. The aim of this study to evaluate the risk of serious adverse outcomes in patients with COVID-19 by stratifying the comorbidity status. We conducted a retro-prospective study of 405 patients admitted into the Mugda Medical College and Hospital, Dhaka,Bangladesh. Among 405 cases, mean age was 46.33 years. About 216 (53.3%) patients were male. Almost 322 (79.5%) patients were managed inside Dhaka city. The most common symptom was fever on or after hospitalization (71.9%). Of the 405 cases the prevalence of specific comorbidities was: hypertension (n=141, 34.8%), other cardiovascular diseases (n=42, 10.4%) cerebrovascular diseases (n=7, 1.7%), diabetes (n=140, 34.6%), COPD (n=4, 1.0%), chronic kidney diseases (n=65, 16.0%), malignancy (n=4, 1.0%) and asthma (n=51,12.6%). Overall, 307 (75.8%) patients discharged alive during the time frame of this study. 98(24.2%) patients died, 63 (15.6%) were admitted to the ICU and 16 (4.0%) received invasive ventilation. Patients with comorbidities should take all necessary precautions to avoid getting infected with SARS CoV-2, as they usually have the worst prognosis. There is a need for a global public health campaign to raise awareness, on reducing the burden of these comorbidity illnesses causing deaths in COVID-19- infected patients. Bangladesh Med J. 2020 Jan; 49 (1): 19-25